Post weld heat treatment of thermo - mechanical controlled process steel - Seow, Zhi Yi (2015)
High strength steel (HSS) has numerous advantages in applications. Thermo mechanical controlled process (TMCP) steel is one popular type due to the benefits of its fine-grained microstructure which improves ductility, toughness and weldability. The recent increase in use of HSS and the fact that current TMCP steel utilize recent technology for accelerated cooling are reasons for the lack of research on existing TMCP steel, particularly regarding how mechanical property changes after welding and post weld heat treatment. This research investigates the effect of welding and post weld heat treatment (PWHT) on 22mm thick S460M TMCP steel plates with a focus on ductility. Tensile coupon tests carried out ascertained that welding caused a 11.1% reduction in ductility while PWHT allowed 58.9% recovery of the ductility loss. By varying PWHT parameters, optimal holding temperature and times of 540°C for 210 minutes were identified. Samples extracted for microstructure examination revealed how reduction in ductility was accompanied by an increase in grain size complementing the understanding of the effects of welding and PWHT. Thereafter, the effect of PWHT on 16mm and 22mm thick T-stub joints was studied to validate findings of tensile coupon tests in actual welding application. Brittle failure at the HAZ was observed, indicating reduced ductility. Yield strength values were obtained from the force-displacement graph. Numerical analysis (finite element (FE) analysis and yield line analysis) and EC3 design formula were used to find yield strength. By comparing that with experimental yield strength values, EC3 values were found to be conservative hence valid for design use while FE analysis and yield-line model were found to overestimate the yield strength for both 16mm and 22mm S460M T-stub joints. Overall, the effect of welding reducing ductility of a 22mm thick plate was insignificant although PWHT itself remained an effective process to regain ductility of steel HAZ. In addition, EC3 design formula is valid and accurate for 16mm and 22mm welded plates.